Pertanggungjawaban Manajemen RS PHC Surabaya dalam Perekrutan Praktik Dokter Ilegal berdasarkan Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan - Sari, Jayanti Purnama; Santosa, Anak Agung Gede Duwira Hadi; Kartika, I Gusti Ayu Putri; Winata, I Gde Sastra (Syntax Corporation, 2024)
The case of an illegal doctor named Susanto who worked at Primasatya Husada Citra Surabaya Hospital for approximately 3 years has troubled the community in Surabaya City. This study aims to determine the role of the Hospital Medical Committee of Primasatya Husada Citra Surabaya Hospital in supervising the recruitment process of doctors and the implications for patients who get the wrong dose and/or actions performed by illegal doctor Susanto. The research method used is normative juridical which involves analyzing documents or secondary data. The approach used in this research is qualitative research and is presented descriptively. The results showed that the Medical Committee of PHC Surabaya Hospital did not succeed in carrying out its duties optimally, thus allowing Susanto, who was actually unqualified, to obtain a position as an illegal doctor. The implication for patients who received the wrong dose and/or action performed by the illegal doctor Susanto is that the patient has the right to file a lawsuit to obtain compensation and justice. Lawsuits can be in the form of criminal charges and civil suits.